2002
DOI: 10.1111/j.1559-1816.2002.tb02069.x
|View full text |Cite
|
Sign up to set email alerts
|

The Good‐Mother Stereotype: Stay at Home (or Wish That You Did!)

Abstract: This study extends prior research on the good‐mother stereotype by examining the influence of mothers’ role satisfaction on perceptions. Students read a brief description of a mother and rated her commitment to motherhood and communality. As predicted, the mother who remained home with her child and who was satisfied with staying home was rated higher than was the dissatisfied stay‐at‐home mother. However, the continuously employed mother who was satisfied with working outside of the home was perceived as less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…The increased employability of women who have experienced multiple periods of unemployment is consistent with a perception that those female applicants may have done so voluntarily to manage responsibilities of work and family (Gorman & Fritzsche, 2002;Wayne & Cordeiro, 2003), and now are ready to reenter the workforce on a continuous basis. In parallel, gender-role theory suggests that individuals may suffer penalties when their behaviors are inconsistent with expected gender roles (Lovell et al, 1999).…”
Section: Discussionmentioning
confidence: 67%
“…The increased employability of women who have experienced multiple periods of unemployment is consistent with a perception that those female applicants may have done so voluntarily to manage responsibilities of work and family (Gorman & Fritzsche, 2002;Wayne & Cordeiro, 2003), and now are ready to reenter the workforce on a continuous basis. In parallel, gender-role theory suggests that individuals may suffer penalties when their behaviors are inconsistent with expected gender roles (Lovell et al, 1999).…”
Section: Discussionmentioning
confidence: 67%
“…'Good' motherhood is conceptualised as full-time, intensive, and child-centred (Hays, 1996), and sex-role stereotype studies continue to show that perceptions of 'good' mothers are commensurate with full-time stay-at-home mothers, rather than those in employment (e.g. Gorman & Fritzsche, 2002). Maher and Saugeres (2007) found that women without children held an idealized view of full-time, intensive motherhood (Hays, 1996) which they saw as incompatible with employment and other aspects of their identities and life plans, indicating that discourses of 'good', full-time motherhood may shape women's decisions around childbearing.…”
Section: Older Motherhood -An Uncomplicated Choice?mentioning
confidence: 99%
“…Moreover, in keeping with a postfeminist era, intensive mothering foregrounds conservative femininities; it 'redefines women, first and foremost, through their relationships to children' (Douglas and Michaels, 2004, p.162). Women who wish to occupy the position of the 'good mother' should stay at home (Gorman and Fritzsche, 2002), the alternative is said to leave women with feelings of guilt for spending time away from children, and without the necessary energy to compete with men for high status and highly paid jobs (Hays, 1996). In short intensive mothering ideology is one means of maintaining women's subordinate position in relation to men (Hays, 1996).…”
Section: Intensive Motherhoodmentioning
confidence: 99%